The art of medicine: myth or reality? A narrative review - Ronald A. Aaron; Linda Jones (Critical Public Health)
The term ‘art of medicine’ (AOM) can be traced back to ancient Egypt. Medical education and practice continue to be influenced by unprecedented technological progress. The increased emphasis on science in the undergraduate medical curriculum came at the expense of studies in the arts and (medical) humanities (MHs). This study conceptualised AOM and rendered its characteristics visible in an attempt to confirm or dispel its reality. We used a narrative literature review and qualitative methodology to determine (1) How is AOM conceptualised and defined within the literature? (2) What are its characteristics or attributes? and aimed to (3) theorise and contribute to ongoing discourse. Our methods extend beyond the usual narrative summary and thematic analysis to develop an interpretative layer of understanding by using thematic synthesis for data analysis. We identified the attributes/codes and concepts/themes of AOM based on the levels of abstraction, with themes being more abstract. Further interpretation produced a typology of nine major concepts ranked as a concept system according to decreasing levels of abstraction. These nine major concepts are ‘Obligation and opportunity’, ‘Way of life’, ‘Art of healing’, ‘Mastery’, ‘Manage uncertainty’, ‘Empathy’, ‘Caring skills’, ‘Effective communication’, and ‘Relationships’. Thematic analysis and synthesis allowed us to disaggregate AOM into common, easily understandable, and accessible building blocks. In so doing, we believe we were able to transform AOM from a nebulous concept into structured reality. Our analysis and interpretations may provide a framework for the deliberate learning and teaching of AOM, thus restoring its central position in medical education and practice.